MEMBANGUN BIROKRASI UNTUK GOOD GOVERNANCE (Relasi Pejabat Politis dan Pejabat Birokratis pada Pemerintahan Lokal Untuk Mewujudkan Good Governance - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; Nanang Haryono (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2010)
Direct regional head elections (pilkadal) indeed has been promoting the democratic process in Indonesia. However, legislators and regional head of the process results in the execution of his duty pilkadal often there are obstacles in carrying out their duties. This is because the vision that was brought by members of parliament and elected local leaders are often influenced by the spirit of the political party that carried him. The logic used by legislators and local leaders are not elected public servant, but rather the logic of the logic of political servants. The problem posed then is the relationship between elected officials (politicians) and appointed officials (official bureaucracy) to be not in harmony and result in implementing the stunted development.